Do it effective the implementation e-procurement in Public Contract? (2017)
This article consist analyze the process of implementing of the new version of SECOP II, as a new electronic procurement system in Colombia the progress it has made, its benefits in the use of the system and its drawbacks In addition to this, it is sought to investigate the international influences and policies that Colombia seeks to penetrate about public contractual processes by joining the Organization for Economic Co-operation and Development (OECD) And to diagnose the experience of different countries of the world belonging to this organization in order to verify if the implementation of this system to the public administration is really effective.